Mortality - Hitchens, Christopher (New York : Twelve, 2012)
"Courageous, insightful and candid thoughts on malady and mortality from one of our most celebrated writers"-- Provided by the publisher.
On June 8, 2010, while on a book tour, Hitchens was stricken in his New York hotel room with excruciating pain in his chest and thorax. Over the next eighteen months, until his death in Houston on December 15, 2011, he wrote constantly and brilliantly on politics and culture. Hitchens poignantly describes the torments of illness, discusses its taboos, and explores how disease transforms experience and changes our relationship to the world around us.
Keywords: Hitchens, Christopher -- Health; Cancer -- Patients -- United States -- Biography; Terminally ill -- United States -- Biography; Mortality; Death; Authors, American -- Biography; Large type books